CHRONIC OBSTRUCTIVE LUNG DISEASE AS RISK FACTOR FOR CARDIOVASCULAR DISORDERS - A. V. Budnevsky; E. Yu. Malysh (Кардиоваскулярная терапия и профилактика, 2016)
Close relation of cardiovascular (CVD) diseases and chronic obstructive pulmonary disease (COPD) gains attention during last years as one of the aspects of systemic COPD signs. High prevalence of CVD in COPD patients can be explained by a concept of persisting systemic lowintensive inflammation. Current review regards COPD as risk factor for CVD that demands respective multidisciplinary diagnostic and management approaches.